Role of microstructural white matter changes of somatosensory cortex in stress among non-clinical population: a diffusion tensor imaging study - Abd Razak, Wan Adibah Nadiah; Shamsuddin Perisamy, Rajeev; Zulkifli, Nor Saradatul Akmar; Abdul Basit, Khairul Salleh; Mustapha, Muzaimi; Zolkefley, Mohd Khairul Izamil (International Islamic University Malaysia, 2024)
INTRODUCTION Stress is a common response to stressors or perceived threats, resulting in physical, affective, and cognitive changes. Emotional processing is closely linked to interpretations of physiological changes, which largely depend on the somatosensory cortex, including the postcentral gyrus. The objective of this study was to examine the correlation between stress and alterations in the microstructure of white matter in the somatosensory cortex among a healthy, non-clinical population.